1984
DOI: 10.1002/jat.2550040104
|View full text |Cite
|
Sign up to set email alerts
|

The neurotoxicity of trimethyltin chloride in hamsters, gerbils and marmosets

Abstract: Trimethyltin chloride (TMT) was given to Syrian hamsters, gerbils and marmosets, and the changes in the brain were studied 1 day to 7 weeks later by light and electron microscopy. Within the marmoset brain, TMT was found to be uniformly distributed, similar to that in the rat. In all three species, signs of poisoning included whole-body tremors and prostration, while death might occur in 3-4 days; in marmosets ataxia, agitation, aggression and occasional fits were also observed. Bilateral symmetrical neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…The influence of trimethyltin on rodent behavior has received much attention, and was recently summarized by McMillan and Wenger (1985). In monkeys intoxicated with trimethyltin, similar behavioral and neuropathologic alterations were noticed as in rodents (Brown et al, 1984;Reuhl et al, 1985). Also for humans accidentally exposed to trimethyltin a variety of psychomotor changes were reported, including irritability, depression, aggressiveness, headaches, tremors, convulsions, and changes in libido (Fortemps et al, 1978;Ross et al, 1981).…”
Section: Neurotoxicitymentioning
confidence: 83%
“…The influence of trimethyltin on rodent behavior has received much attention, and was recently summarized by McMillan and Wenger (1985). In monkeys intoxicated with trimethyltin, similar behavioral and neuropathologic alterations were noticed as in rodents (Brown et al, 1984;Reuhl et al, 1985). Also for humans accidentally exposed to trimethyltin a variety of psychomotor changes were reported, including irritability, depression, aggressiveness, headaches, tremors, convulsions, and changes in libido (Fortemps et al, 1978;Ross et al, 1981).…”
Section: Neurotoxicitymentioning
confidence: 83%
“…TMT is a by-product of DMTC manufacture 7) . A previous report showed that 8% of TMT was produced as a by-product of DMTC 10) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that dimethyltin chloride is toxic to the liver and kidneys, whereas trimethyltin chloride damages the central nervous system [2][3][4] . The neurotoxicity of dialkyltin or trialkyltin compounds has been recognized in animal studies, but only a few descriptions of their human toxicity have been reported 1,[5][6][7][8][9][10][11][12][13][14] . Especially, reports of human dimethyltin intoxication are very rare 15) .…”
mentioning
confidence: 99%
“…It is very likely, in the animal body, that some of the chloride ions are substituted by hydroxide ions so that both hydroxides and chlorides are present; since both forms a re soluble in water and in lipids, the rapid passage of trimethyltin through the cellular membranes is possible. The presence of significant amounts of trimethyltin in the nervous system is compatible with the occurrence of pathologic changes; however, there is no evidence that the selective damage of certain neurons is associated with focal concentrations of trimethyltin (Brown et al 1984b). Additional factors, such as the functional state of neurons with hyperactivation of selected systems, may account for their particular vulnerability (Chang and Oyer 1985).…”
Section: Etiology and Pathogenesismentioning
confidence: 96%